2012
DOI: 10.1074/jbc.m112.384909
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2 Cleavage of the β1 Integrin Ectodomain Facilitates Colon Cancer Cell Motility

Abstract: Background: Cancer cell invasion requires integrins for adhesion/de-adhesion and MMPs for focalized proteolysis. Results: MMP-2 is up-regulated in invasive colorectal tumors and degrades ␤1 integrins. Conclusion: Shedding of the I-like domain from ␤1 integrins results in decreased adhesion and enhanced cell motility. Significance: MMP-2 amplifies the motility of cancer cells, not only degrading extracellular matrix but also reducing the ␤1 integrin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 37 publications
1
52
0
1
Order By: Relevance
“…These multi-functional degrading enzymes play a critical role in carcinogenesis but also in other stages of the invasion-metastasis cascade. CRC cells may induce the expression of MMP-2 and -9 by stromal cells, either directly or via a paracrine mechanism, thus modifying ECM and promoting tumour development [56][57][58] .…”
Section: Lymphocytesmentioning
confidence: 99%
“…These multi-functional degrading enzymes play a critical role in carcinogenesis but also in other stages of the invasion-metastasis cascade. CRC cells may induce the expression of MMP-2 and -9 by stromal cells, either directly or via a paracrine mechanism, thus modifying ECM and promoting tumour development [56][57][58] .…”
Section: Lymphocytesmentioning
confidence: 99%
“…It was reported that the critical step for invasion and metastasis is the breakdown of the basement membrane, which involved the activation of proteolytic enzymes such as MMPs. MMPs play an important role in tumor angiogenesis, metastasis and stimulation of growth factor release from the ECM (Kryczka et al, 2012). Numerous studies indicate that inhibition of MMP expression or enzyme activity can be used as early targets for preventing cancer metastasis (Zucker & Vacirca, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs), a family of human zinc-dependent endopeptidases, degrade the ECM (Junttila et al, 2007;Liang, 2011). Among them, the gelatinases (MMP-2 and MMP-9) efficiently degrade native collagen types IV and V, fibronectin and elastin (Kryczka et al, 2012). MMP-9 activity can be stimulated by various growth factors and proinflammatory cytokines and agents, including phorbol 12-myristate 13-acetate (PMA) (Woo, Park, Choi, Kim, & Kim, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-2 was shown to be an important factor associated with the development and metastasis of gastric and colorectal cancer and may be used as a prognostic marker (108,109).…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%